2x(x-2)+3x(x-3)=1

Simple and best practice solution for 2x(x-2)+3x(x-3)=1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x(x-2)+3x(x-3)=1 equation:



2x(x-2)+3x(x-3)=1
We move all terms to the left:
2x(x-2)+3x(x-3)-(1)=0
We multiply parentheses
2x^2+3x^2-4x-9x-1=0
We add all the numbers together, and all the variables
5x^2-13x-1=0
a = 5; b = -13; c = -1;
Δ = b2-4ac
Δ = -132-4·5·(-1)
Δ = 189
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{189}=\sqrt{9*21}=\sqrt{9}*\sqrt{21}=3\sqrt{21}$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-13)-3\sqrt{21}}{2*5}=\frac{13-3\sqrt{21}}{10} $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-13)+3\sqrt{21}}{2*5}=\frac{13+3\sqrt{21}}{10} $

See similar equations:

| 7-6y=3y×4-47 | | 11x-9=3x+8 | | 10|2x-5|+10=110 | | (3x-45)=(5x-105) | | x+13=10-2x | | v/5=−1 | | 14=2*(3x+1) | | 14=2*(3x+1 | | (2−2x)/11=−12 | | -x+17=2x-1 | | 30=5*(x+1) | | 5+3b=360. | | -2x-7=2x-15 | | 5(3c-2)=40-2c | | 6x+14=2x-18 | | 5x-12=6x+9 | | 5(6y-8)-7(12y+6)=5*3y-7(5y+2) | | 4*(x+3)=24 | | 2/7(3y-4)-3/5(4+2)=3y/7-5y+2/5 | | 4x+10=-56-7 | | 4x+10=56-7x | | y^2+11y+36=0 | | x/20=20 | | 2(a+4)+6=(3a-6) | | 6x+9=17−2x | | 3(x-1)-2×=4(×-2)-1 | | 11x+1=12−4x | | 8)6x+1=7x+11 | | 8x-15=-2x+25 | | 2x+7=27÷2 | | 5x-3x-15=7+4+3x | | √x=10−4 |

Equations solver categories